1968
DOI: 10.1149/1.2411450
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Sodium Migration in Silicon Nitride Films

Abstract: Silicon nitride films deposited on silicon substrates by several techniques were studied. Electron diffraction studies of the films revealed that films varied in crystallite size from <10 to ∼100Aå. Radiotracer diffusion experiments using Na22 as diffusant revealed that the smaller crystallite films were better barriers to sodium diffusion than the larger crystallite films. Field enhanced drift of sodium was not observed in any of the silicon nitride films regardless of crystallite size. Silicon nitride films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1972
1972
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…This should be regarded as a state-of-the-art result developed by unconventional alkaline addition, as a conventional NaOH alkaline addition brings very unstable device behavior. 44 According to other respective PECCS plots and photo-transfer curves of Fig. 6a and 6b, the BTS-imposed IGZO TFT with SiO 2 /Na-containing Ni/Cu gate shows significant photo-shift of V th , along with several intense trap DOS peaks, some of which are located at the same energy levels as those found in the IGZO TFT with H-containing SiN x layer (see Fig.…”
Section: Resultsmentioning
confidence: 61%
“…This should be regarded as a state-of-the-art result developed by unconventional alkaline addition, as a conventional NaOH alkaline addition brings very unstable device behavior. 44 According to other respective PECCS plots and photo-transfer curves of Fig. 6a and 6b, the BTS-imposed IGZO TFT with SiO 2 /Na-containing Ni/Cu gate shows significant photo-shift of V th , along with several intense trap DOS peaks, some of which are located at the same energy levels as those found in the IGZO TFT with H-containing SiN x layer (see Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Using a modified Sirtl etch, a correlation between mounds and dislocations has been reported recently (3). However, the effectiveness of the etch is hindered due to the formation of numerous mounds of various sizes which do not appear to be related to dislocations.…”
Section: Dow Coming Corporation Solid State Research and Developmentmentioning
confidence: 98%
“…14,15,16 Other investigators made incremental reliability improvements over the next few years, with the most fundamental advance coming from J. V. Dalton at Bell Labs in 1966. 17 He showed that an overcoating of silicon nitride would provide an effective seal against alkali ions, mainly sodium. Silicon nitride provided a tough surface passivation and paved the way for the era of low-cost plastic packages with acceptable reliability.…”
Section: Toward Large Scale Integrationmentioning
confidence: 99%